DEVELOPMENT OF MEDIA DOMINO CARD ON MATERIAL TEMPERATURE AND CHANGES IN CLASS VII SMP/ MTs - Fitri Nikmaturrofidah; Oktaffi Arinna Manasikana (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2022)
This study aims to describe the process of developing domino science learning media on the material of temperature and its changes in class VII SMP/MTs based on the ADDIE development procedure and to describe the product developed after the validation, practicality and effectiveness process. This development research uses the ADDIE development model, namely, Analyze, Design, Development, Implementation, and Evaluation. Data were obtained using media validation sheets, material validation sheets, implementation sheets for using domino card science learning media, student response questionnaire sheets and posttest question sheets. The results of the research on the development of domino card science learning media on the temperature material and its changes that have been developed resulted in 3 drafts of domino card science learning media that have received suggestions and input from supervisors and validators, namely media experts, materials and science teachers. The results of the validator's assessment of the domino card science learning media obtained an average score of 3.82 from media expert validators, and 3.25 from material expert validators in the "Very Valid" category. The results of the implementation showed the percentage of implementation was 94.45% with the "Very Practical" category. The results of student responses obtained an average positive response of 96.88% with the category "Very Practical". Based on the posttest data, the overall average score is 84.37 and the average completeness is 75% with the "Effective" category. 25 of the material expert validators in the "Very Valid" category. The results of the implementation showed the percentage of implementation was 94.45% with the "Very Practical" category. The results of student responses obtained an average positive response of 96.88% with the category "Very Practical". Based on the posttest data, the overall average score is 84.37 and the average completeness is 75% with the "Effective" category. 25 of the material expert validators in the "Very Valid" category. The results of the implementation showed the percentage of implementation was 94.45% with the "Very Practical" category. The results of student responses obtained an average positive response of 96.88% with the category "Very Practical". Based on the posttest data, the overall average score is 84.37 and the average completeness is 75% with the "Effective" category.